Analysis of the operation and maintenance of swimming pools in the city of Maracaibo, Venezuela - Carrasquero Ferrer, Sedolfo; Mendoza Guillén, Allen; Pino Rodríguez, Jean; Jativa Castillo, Héctor; Díaz Montie, Altamira (Revista Universidad de Guayaquil, 2024)
Swimming pools, as public and private facilities, must be constantly regulated by public authorities to protect water quality and public health. The objective of this research. was to analyze the operation and maintenance of swimming pools located in the city of Maracaibo, Venezuela, in three areas: treatment and recirculation system, security, and maintenance and cleaning system, in accordance with the provisions of current Venezuelan regulations. To collect data in the diagnosis, direct observation techniques were used and as an instrument an observation guide with an estimation scale, analyzing nine aspects such as: location, appearance of the water, structure of the vessel, materials and dimensions, water drainage , basic maintenance, treatment system, provisions for facilities and operators, rescue equipment and children's pool, grouped into three areas, effectiveness of treatment and recirculation, safety and effectiveness in maintenance and cleaning. It was found that 80% of the study units presented generally good conditions in their facilities, rated according to the instrument with 80.5 points on average; However, certain pools presented deficiencies in some aspects, especially those related to the appearance of the water, location, drainage system and in most pools, the treatment system. It is concluded that 90% of the study units were moderately safe, largely complying with the requirements of Venezuelan regulations in terms of material aspects, dimensions and rescue equipment.
Keywords: recreational waters; technical functioning and operability; swimming pools